Penerapan Metode Fuzzy Service Quality dalam Analisis Kepuasan Pelayanan Kesehatan - Febriani Safitri; Suryati Sitepu; Esther Sorta Mauli Nababan; Parapat Gultom (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Fuzzy logic is an element of Boolean logic, where fuzzy logic is used to handle the concept of degrees of truth between true and false (Yanif, et al, 2011; Henny, 2018). Fuzzy logic theory also provides a method for representing uncertainty and is an excellent tool for modeling uncertainty related to vagueness. To obtain the level of service satisfaction for patients, it can be seen from the difference between the services provided to patients and the patient's expectations. Padang Sidempuan General Hospital is a health service provider. The increase and decrease in patients in the hospital can be caused by the results of the services provided by the hospital to patients. The more patients feel safe and comfortable, the number of consumers will also increase. The method that is relevant to this problem is the Servqual approach combined with Fuzzy theory to measure the patient's gap in perception and expectations precisely. The results of this research are that almost the entire gap value between expectations and perceptions has a negative gap value, thus it can be concluded that the quality of service provided by the hospital is considered not able to meet patient expectations as it should. The research results obtained were that the attribute that was considered the best by patients was the comfort condition of the patient room at Padang Sidimpuan General Hospital with a gap value of 2.913979. Meanwhile, the lowest rated attribute lies in officers not ignoring patients when on duty with a gap value of 50.90728975.